A Diagnostic Mimic of Lung Cancer: Nodular Pulmonary Amyloidosis Presenting With Cystic Changes - Supriya Peshin; Vaishnavi Kulkarni; Faizan Bashir; Rafi Iftekhar; Jaimin Kapadia; Mabe Donovan; Elie Nader (Respirology Case Reports)
ABSTRACT Pulmonary amyloidosis is an uncommon but clinically significant disorder characterised by extracellular deposition of misfolded amyloid fibrils in lung tissue, either as part of systemic disease or as a localised entity. We present a case of a 62‐year‐old man with coal workers' pneumoconiosis and a 40 pack‐year smoking history, who developed progressive dyspnea, chronic cough, and weight loss. Initial chest CT revealed bilateral thin‐walled pulmonary cysts without nodularity. Over several years, the cystic lesions evolved, with interval development of a mural nodule in the right lower lobe. PET imaging was non‐avid, and bronchoscopy yielded nondiagnostic cytology. A left lower lobe wedge resection, performed for a surgically accessible stable cyst, confirmed localised AL (kappa) nodular pulmonary amyloidosis on Congo red staining. Hematologic workup demonstrated an elevated kappa/lambda free light chain ratio without evidence of systemic or cardiac involvement. The patient remains clinically stable under multidisciplinary surveillance. This case illustrates the diagnostic complexity of pulmonary amyloidosis and underscores the importance of including it in the differential diagnosis of cystic lung disease, particularly in the setting of occupational exposure and indeterminate imaging.